Deciphering Direct and Indirect Effects of Neurokinin B and GnRH in the Brain-Pituitary Axis of Tilapia - Mizrahi, Naama; Gilon, Chaim; Atre, Ishwar; Ogawa, Satoshi; Parhar, Ishwar S.; Levavi-Sivan, Berta (Frontiers in Endocrinology, 2019)
Neurokinin B (NKB) and its cognate receptor (NK3R) are emerging as important components of the neuroendocrine regulation of reproduction. Unlike mammalian tac3, which encodes only one mature peptide (namely NKB), two mature peptides are predicted for each tac3 gene in fish and frogs. Therefore, it was designated as Neurokinin F (NKF). Hormone analogs with high and long-lasting biological activity are important tools for physiological and biological research; however, the availability of piscine-specific analogs is very limited. Therefore, we have developed specific NKB and NKF analogs based on the structure of the mammalian NKB analog - senktide. These analogs, specifically designed for longer half-lives by methylation of proteolysis sites, exhibited activity equal to those of the native NKB and NKF in short-term signal-transduction assays of tilapia NKB receptors. However, the analogs were found to be able to significantly increase the release of luteinizing hormone (LH), follicle stimulating hormone (FSH) and growth hormone (GH) in tilapia, as fast as 1 hour after intraperitoneal (IP) injection. The impact of the analogs on LH and FSH secretion lasted longer compared to the effect of native peptides and salmon GnRH analog (sGnRHa). In addition, we harvested pituitaries 24 hours post injection and measured LH, FSH and GH mRNA synthesis. Both analogs elevated mRNA levels of LH and GH, but only NKB analog increased FSH mRNA levels in the pituitary and all GnRH forms in the brain. NKB receptors were co-localized with all three types the GnRH neurons in tilapia brain in situ. We previously showed a direct effect of NKB at the pituitary level, and these new results suggest that the stronger impact of the NKB analog on GTH release is also due to an indirect affect through the activation of GnRH neurons. These results suggest that novel synthetic NKB analogs may serve as a tool for both research and agricultural purposes. Finally, the biological activity and regulatory role of NKB in tilapia brain and pituitary suggest that the NKB/NKBR system in fish is an important reproductive regulator in a similar way to the kisspeptin system in mammals.